PENGELOLAANDAYATARIKWISATAWATERFRONTCITY PANGURURAN KABUPATEN SAMOSIR - Tamba, Ria Natalia; Situmeang, Lestari; Sitanggang, Yesica (Jurnal Ilmiah Akomodasi Agung, 2025)
This Study a imstoidentify the condition of available facilities and infrastructure as well as to analyze visitor management effort susing the Visitor management approachat Waterfront City Pangururan. The method used is descriptive qualitative, with data collection techniques including observation, interviews, literature review, and documentation. The results showthat facilities and infrastructure at Waterfront City Pangururan are generally available, such as tourist attractions, thematic parks, aesthetic bridges, culinary centers, information facilities, road access, electricity, clean water, internetnet works, and health facilities. However, their utilization has not been fully optimal interms of quality and equitable distribution across the entirearea. In addition, several facilities were found to be damage dand poorly maintained. Regarding visitor management, the management has referred to the principles of Visitor Management, yet the implementation of visitor limits based on Physical Carrying Capacity has not been carried out optimally. In conclusion, the management of the area has been implemented but still require simprovement sinvarious aspects sothat this destinationcan develop into a comfortable, orderly, and sustainable tourist attraction.